Characterization of a novel trithorax group gene candidate in Arabidopsis - Liang, Shih-Chieh (The University of Edinburgh, 2013)
The Polycomb group (Pc-G) and trithorax group (trx-G) genes play crucial roles in development by regulating expression of homeotic and other genes that control cell fate. Both groups catalyse modifications in chromatin, including histone methylation, leading to epigenetic changes in gene activity. The trx-G antagonises the function of Pc-G genes by activating Pc-G target genes, and consequently trx-G mutants suppress Pc-G mutants. The trx-G genes are relatively poorly characterised in plants. We identified a novel trx-G candidate SUPRESSOR OF POLYCOMB 12 (SOP12) by a genetic screen for suppressors of mutants for the Arabidopsis Pc-G gene CURLY LEAF (CLF). Thus sop12 mutations have no discernible phenotype in wild type backgrounds but partially suppress the leaf curling and early flowering phenotypes of clf mutants. Molecular cloning shows that SOP12 encodes a Harbinger transposase nuclease-like protein which is conserved in green plants, although key residues required for the catalytic activity of the nuclease domain are not conserved. In sop12 clf double mutants, many CLF target genes are down-regulated relative to clf mutant, which suggests SOP12 is a general activator of Pc-G target genes instead of a target of CLF or a late flowering suppressor. The CLF gene encodes an H3K27me3 histone methyltransferase, however chromatin immunoprecipitation (ChIP) analysis indicates that SOP12 does not antagonise Pc-G by removing H3K27me3 methylation, which is consistent with the fact that sop12 suppresses mutants for another Pc-G gene, LIKE HETEROCHROMATIN PROTEIN 1 (LHP1), which is not involved in H3K27me3 deposition. Rather, genetic analysis shows that sop12 enhances the phenotype of mutants of EARLY FLOWERING IN SHORT DAYS (EFS), a trx-G gene involved in deposition of H3K36me3, and of ULTRAPETALA 1 (ULT1), a plant specific trx-G gene. The enhancement indicates SOP12 may act together with ULT or EFS proteins, or at least regulate the same targets in synergistic ways. For example, SOP12 activates AP3 expression, a role which overlaps with EFS. Yeast two hybrid screening and imunoprecipitation followed by Mass spectrometry were performed to identify numerous potential SOP12 interacting proteins but await further validation. One protein (SUP1) identified through yeast two hybrid screens was independently identified by another group as a Pc-G suppressor, suggesting that SOP12 and SUP1 may act in a common complex to regulate Pc-G targets. Collectively, my data suggests that SOP12 represents a domestic transposase that has acquired a role as a novel, plant specific trx-G members.
Keywords: Polycomb group; trithorax group; epigenetics